Vietnam : Formal and Informal Social Assistance in Metropolitan Cities - A Rapid Assessment - Nguyen, Tam Giang (World Bank, Washington, DC, 2013)
The expanding coverage of social assistance in Vietnam raises a question of whether relevant arrangements at all levels are sufficiently robust to handle a larger program. This note explores institutional and delivery aspects of formal and informal social assistance in metropolitan cities. It is a result of a rapid assessment of governance and administration of social assistance in metropolitan cities, including interviews with related stakeholders in Ho Chi Minh City in July 2010 and in Hanoi in January 2011. Basically, the existing governance and administrative structures for delivery of Decrees 67/13 assistance in Hanoi and Ho Chi Minh City are characterized by a number of common issues elsewhere in the country, as described in previous studies. In addition, this note finds that while the cities may have resources to self-finance their assistance under Decrees 67/13 and provide significant informal assistance through various channels, their determination of exclusive poverty lines without sound scientific grounds may result in substantial inclusion and exclusion errors in locally funded schemes of aid. Furthermore, although the cities provided some forms of off-budget temporary assistance in response to the economic crisis in 2009, their targeting was based on the poor list and the 'conventional' administrative classification of residence status rather than consideration of actual needs as arisen from the crisis. These findings entail systematically strengthening the governance and administrative system of social assistance, given proven substantial increases in beneficiary coverage under Decree 13; improving methods of determining poverty lines; and developing measures to identify emerging needs from external catastrophic shocks and thus formulating an appropriate targeting mechanism in the metropolitan cities. Also, a mechanism is required to effectively harmonize formal and informal assistance in order to optimize resources and maximize the coverage of assistance to needy individuals and households.